14-Methoxy-2,16-dioxapentacyclo[7.7.5.01,21.03,8.010,15]henicosa-3(8),10,12,14-tetraene-7,20-dione - Lu, Weicheng (International Union of Crystallography, 2011)
The title compound, C20H20O5, was synthesized from the reaction between 3-methoxysalicaldehyde and 1,3–cyclohexanedione in the presence of palladium(II) chloride. The two fused xanthene rings and one of the six-membered cyclohexane rings adopt envelope conformations, while the other six-membered cyclohexane ring is in a chair conformation. The molecular packing is stabilized by weak intermolecular C—H⋯O interactions.